Prospects for the digital transformation of the “Affordable medicines” program and cooperation with the European union market of medical products - Smirnova, Hanna (Journal of Education, Health and Sport, 2022)
The year 2023 the world marked as the anniversary of the full-scale invasion of russian troops into Ukraine and the beginning of the largest war of the XXI century. Each spectrum of the sphere of social service and provision is fighting on its own front, trying to optimize the standard of living of the civilian population of Ukraine as much as possible. At the same time, the concept of “population quintiles” in our war days ceased to be a purely economic concept, and became rather a sociological one. In our opinion, today there are two really fundamental groups of the civilian population of Ukraine: Ukrainians who will continue to live in their cities and regions, as well as internally displaced persons (that is, a group of citizens who have not left the territory of Ukraine) on the one hand, as well as externally displaced persons, who became refugees mostly in European countries, on the other hand. As for January-February 2023, about 5.12 million Ukranian refugees were registered in Europe, while the Ministry of Foreign Affairs gives a much higher number - namely, about 7.9 million people [41]. At the same time, both official sources note that this figure is 97% among all immigrants from Ukraine who received refugee status in the world. Thus, we must also take into account the fact that there are an untold number of individuals who have not been granted the above status because they were on various grounds abroad prior to the start of the full-scale invasion; those, who have already lived abroad for a long or short time; as well as those, who are still waiting for recognition of their right to be a refugee on the territory of some EU countries, because not everywhere this process is optimized and fast enough. Thus, it is worth assuming that the real number of Uktainians living abroad in one way or another is at least twice or even three times higher. And, therefore, this fact directly affects the immediate need to provide this huge number of people with appropriate social and medical livelihoods, which are the main postulates of the development of the Affordable Medicines (AM) program. Today, the issue of the AM program going internation is no longer a matter of reflection but the main direction of its development in the near future. Such statements arise due to the future very high probability of a sharp jump in the populaion’s rates of oncological diseases, as well as the question of optimizing the frankly crisis system in the field of health care in the EU cuntries. In other words, the sharp and almost uncontrolled influx of a large number of refugees, epecially to the countries closest to the western border of Ukraine, led to serious problems with access to medical care not only for refugees themselves, but also for the citizens of this country [37-40]. Objectively, the main directions of our research today are: development of ways to optimize the medical life support system of citizens of EU countries and refugees due to cooperation with professionals of the AM program; as well as the developent of optimal ways of combating the spectrum of oncological diseases, which will become one of the fatal consequences of the post-war period of Ukraine’s development, likewise one of the EU countries, if those ways of combating the above-mentioned phenomena are not developed now.